First total synthesis of kipukasin A - Li, Chuang; Ding, Haixin; Ruan, Zhizhong; Zhou, Yirong; Xiao, Qiang (Beilstein Journal of Organic Chemistry, 2017)
In this paper, a practical approach for the total synthesis of kipukasin A is presented with 22% overall yield by using tetra-O-acetyl-β-D-ribose as starting material. An improved iodine-promoted acetonide-forming reaction was developed to access 1,2-O-isopropylidene-α-D-ribofuranose. For the first time, ortho-alkynylbenzoate was used as protecting group for the 5-hydoxy group. After subsequent Vorbrüggen glycosylation, the protecting group could be removed smoothly in the presence of 5 mol % Ph3PAuOTf in dichloromethane to provide kipukasin A in high yield and regioselectivity.
Keywords: gold catalysis; kipukasin A; marine nucleoside; total synthesis; Vorbrüggen glycosylation